Initial and progressive failure analysis of a composite wing spar structure / Bruce Ralphin Rose.J and Priyadharshini.S - Bruce, Ralphin Rose.J; S, Priyadharshini (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In the present work, a main spar section of a composite wing structure is analyzed for its structural safety in the course of preliminary aircraft design phase. Spar is a spanwise structural member that is used to carry the bending loads and it deals with the self weight of the wing while the airplane is on the ground as well as it carries the lifting loads during flight. Because of the rolling inertia loads and chord wise bending loads caused by aerodynamic effects, spar structure is vulnerable to different structural failures before the end of safe life cycle. Initial and progressive failure analysis of the spar section is done by using the typical properties of composite materials. Carbon epoxy, Graphite epoxy and Boron epoxy materials are analyzed with their standard material properties to determine the crack initiation and propagation characteristics at different time steps with stress increments. A two-dimensional spar cross section (I - section) is designed with shell as element type and the analysis is done in ABAQUS/CAE by using XFEM for crack initiation. The results obtained through the computational analysis show the variation in crack propagation rate for different composites and it can be utilized to study the fracture mechanics in the detailed design phase of an airplane.